(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Incisional hernia is a common complication that arises after midline laparotomy, and it is associated with high morbidity, decreased quality of life and high healthcare costs. A reliable technique for closing the abdominal wall should provide strength and act as a barrier against infection. The method used to close the wound and the type of suture material utilized are critical factors in ensuring an effective abdominal wall closure after midline laparotomy. Abdominal wound dehiscence following closure is a severe complication, particularly in emergency laparotomy. To observe the postoperative outcome of small bite technique and large bite technique in midline incision closure. Materials and methods: This quasi-experimental study was conducted in the Surgery Department of Chittagong Medical College Hospital, Chattogram, over a period of one year from February 2020 to February 2021.A total of 88 patients who underwent emergency midline laparotomy were included in this study. Patients over 18 years old who had laparotomy using an upper midline incision were included. The patients were divided equally into two groups by consecutive technique. Group A consisted of 44 patients using the conventional large bite technique, while Group B consisted of 44 patients using the small bite technique. Window-based computer software using SPSS22 performed statistical analyses. Results: Almost half (43.3%) of patients belonged to age 21-30 years in group A and 21(47.7%) in group B. The male-to-female ratio was 6.3:1 and 10:1 in groups A and B, respectively. There was no significant difference between the two groups (p>0.05). Group A had a wound infection rate of 38.6%, compared to 22.7% in Group B. The mean level of pain (0-10) was 1.95±1.46 in group A and 1.07±1.32 in group B. Group A had Southampton score 01 in 45.5% of patients, compared to 31.8% in group B.The mean characteristics were 1.95±1.46 in group A and 1.07±1.32 in group B. More than one-fourth (27.3%) of patients had wound dehiscence in group A and 5(11.4%) in group B. Three (6.8%) patients had burst abdomen in group A and 2(4.5%) in group B. The difference in level of pain (0-10) and characteristics were statistically significant (p<0.05) between the two groups. Five (11.3%) patients had superficial Incisional surgical site infection in group A and 5(11.3%) in group B. Ten (22.8%) patients had deep Incisional Surgical site infection in Group A and 3(6.8%) in Group B. No patient had organ or space infection in Group A or Group B.The difference in deep incisional surgical site infectionwas statistically significant (p<0.05) between the two groups. 43.3% of patients in group A had a hospital stay lasting 5-10 days, compared to 68.2% in group B. The mean duration of hospital stay was 11.11±3.72 days in group A and 9.18±2.66 days in group B. The difference was statistically significant (p<0.05) between the two groups. No patient had an incisional hernia in group A and group B at one month. The difference was statistically not significant (p>0.05) between the two groups. Five (11.4%) patients had incisional hernia after six months in group A and 2(4.6%) in group B. The difference was statistically not significant (p>0.05) between the two groups. Conclusion: The small bites suture technique is more effective than the traditional largebites technique. JCMCTA 2024 ; 35 (1) : 38-43